Using process mapping, forms and templates for the production of SOPs - Turner, Gareth (Henry Stewart Talks, 2013)
Standard Operating procedures, Application of Process Maps to SOPs – Designs of SOPs using process mapping techniques – Linking associated Forms and Templates to Process Map based SOPs